Perception of the Degree of Importance of Teacher’s Professional Competences from the Perspective of Teacher and Head Teacher in the Evaluation Process of Educational Efficiency - Stranovská, Eva; Lalinská, Mária; Boboňová, Ivana (Pedagogika, 2017)
The research study concentrates on the detection of perception of the degree of importance of selected teacher’s professional competences in the teacher’s evaluation process, i.e. teacher’s success in teaching. Perception of the degree of importance of professional competences of teachers is realized depending on the variables teacher versus head teacher and the degree of importance (1–5). We set up the hypothesis that there are differences in the perception of the importance degree of teacher’s professional competences with respect to teacher and head teacher. We based our assumption on Frey’s evaluation theory, or diagnosis of teacher’s competences and Bandura’s theory of self-efficacy. The research was conducted with 730 respondents from among teachers and 146 respondents from among head teachers of primary and secondary schools in Slovakia during the period from September 2015 to January 2016. Teacher’s perception of the degree of importance of teacher’s professional competences we surveyed using the Teacher’s competence assessment questionnaire for teachers and the head teacher’s perception of the degree of importance teacher’s professional competences using the Teacher’ competence assessment questionnaire for head teachers. The questionnaires were developed within the research project APVV-14-0446 Evaluation of teacher’s competences. We found out that the teachers’ and head teachers’ perception of the degree of importance of various teachers’ professional competences is different. The perception differs in the following professional competences: can identify psychological and social factors of pupil’s learning, can plan and implement their own professional development, can use material resources in the teaching process.